The value of dry bluestem pasture and a comparison of supplements for heifer calves in a wintering, grazing and fattening program. - Smith, E.F.; Koch, B.A.; Good, D.L.; Severns, V.D. (Kansas Agricultural Experiment Station, 2011)
Circular 320 from this station contains a three-year summary comparing heifers wintered in dry lot with heifers wintered on dry grass and the effect of this winter treatment on their total performance in a wintering, grazing, and fattening program. The results of this test showed the heifers wintered on dry grass gained 32 pounds less for the year, had a lower dressing percentage, graded lower, and sold for about $1 a hundred less than heifers wintered in dry lot. However, the heifers wintered on dry grass returned as much money above feed costs as the heifers wintered in dry lot, due primarily to lower winter feed costs and high summer grass gains. In this test the plane of nutrition has been raised slightly for the heifers wintered on dry grass, to acquire some of the desirable characteristics associated with dry-lot wintering, but still maintaining low winter feed costs. In addition different levels of protein supplementation are being compared.
Keywords: Beef; Bluestem; Performance; Nutrition